Competing Expectations in an Index-Based Livestock Insurance Project. Issue 6 (3rd June 2019) - Johnson, Leigh; Wandera, Brenda; Jensen, Nathan; Banerjee, Rupsha
Abstract: Despite donor enthusiasm for index-based microinsurance, globally, pilots have struggled to realise its promises. This paper considers the Kenyan Index-Based Livestock Insurance pilot, investigating the competing expectations held by actors including (re)insurers, researchers, donors, NGOs, and pastoralists. We explore expectations' impacts on partner involvement, project outcomes, sales, and the future outlook for Kenyan livestock insurance. Quantitative analysis suggests early demand and subsequent backlash were not results of systematic mis-selling, but rather stemmed from clients' unfulfilled expectations of patron-like relationships with insurance partners. We caution against exaggerated expectations of profitability and call for reflection and transparency amidst the embrace of insurance tools.